Thermodynamic analysis of a novel integrated geothermal based power generation-quadruple effect absorption cooling-hydrogen liquefaction system - Ratlamwala, Tahir Abdul Hussain (2012)
In this paper, we propose a novel integrated geothermal absorption system for hydrogen liquefaction, power and cooling productions. The effect of geothermal, ambient temperature and concentration of ammonia-water vapor on the system outputs and efficiencies are studied through energy and exergy analyses. It is found that both energetic and exergetic coefficient of performances (COPs), and amounts of hydrogen gas pre-cooled and liquefied decrease with increase in the mass flow rate of geothermal water. Moreover, increasing the temperature of geothermal source degrades the performance of the quadruple effect absorption system (QEAS), but at the same time it affects the liquefaction production rate of hydrogen gas in a positive way. However, an increase in ambient temperature has a negative effect on the liquefaction rate of hydrogen gas produced as it decreases from 0.2 kg/s to 0.05 kg/s. Moreover, an increase in the concentration of the ammonia-water vapor results in an increase in the amount of hydrogen gas liquefied from 0.07 kg/s to 0.11 kg/s.